Nkx2.2 Regulates β-Cell Function in the Mature Islet - Doyle, Michelle J. (2007)
Nkx2.2 is a homeodomain transcription factor that is critical for pancreatic endocrine cell specification and differentiation in the developing mouse embryo. The purpose of this study was to determine whether Nkx2.2 is also required for the maintenance and function of the mature β-cell in the postnatal islet. We have demonstrated previously that a repressor derivative of Nkx2.2 can functionally substitute for endogenous Nkx2.2 to fully restore α- and immature β-cells in the embryonic islet; however, Nkx2.2 activator functions appear to be required to form a functional β-cell. In this study, we have created transgenic mouse lines to express the Nkx2.2-repressor derivative in the mature β-cell in the presence of endogenous Nkx2.2. The transgenic mice were assessed for β-cell function, overall islet structure, and expression of β-cell–specific markers. Using this transgenic approach, we have determined that the Nkx2.2-repressor derivative disrupts endogenous Nkx2.2 expression in adult mice and causes downregulation of the mature β-cell factors, MafA and Glut2. Consistently, the Nkx2.2-repressor mice display reduced insulin gene expression and pancreatic insulin content and impaired insulin secretion. At weaning, the male Nkx2.2-repressor mice are overtly diabetic and all Nkx2.2-repressor transgenic mice exhibit glucose intolerance. Furthermore, the loss of β-cell function in the Nkx2.2-repressor transgenic mice is associated with disrupted islet architecture. These studies indicate a previously undiscovered role for Nkx2.2 in the maintenance of mature β-cell function and the formation of normal islet structure.